The Influence of Participation in PHBM PLUS (Kemitraan Perhutani) on Economic Welfare of Farmers in Wadang Village - Nurrohman, Heru; Prayitno, Gunawan; Wicaksono, Agus Dwi (Perencanaan Wilayah dan Kota FT UB, 2024)
The Kemitraan Perhutani/Perhutani Partnership is a community-based forest management program that is oriented towards two goals, namely forest sustainability and community welfare. This program has been implemented in several areas, one of which is Wadang Village. This program in Wadang Village is supervised and implemented by Perhutani RPH Wadang, KPH Bojonegoro. Implementation of this program involves communities around the forest, especially farmers. Implementing this program in several other areas has had a positive impact on farmers or the community, especially regarding their economy. This research was intended to analyze the influence of the Kemitraan Perhutani/Perhutani Partnership program on the economic welfare of farmers who are members and it is hoped that it can become a basis for developing the economy of the community, especially farmers. This research uses descriptive methods and SEM-PLS to analyze the effect of participation on economic welfare. Samples were taken using the accidental sampling method with a sample of 75 farmers. Next, the survey data will be input into the SEM-PLS model and a simulation will be carried out to determine the effect of participation variables on economic welfare. The results obtained are that the variables participation in planning, participation in implementation, and participation in the utilization of results have values of 3.565; 3.253; and 4.343 respectively. This value has a value range of more than ≥ 1.96 so the participation variable in planning, implementation, and utilization of results has a significant effect on the economic welfare variable. Apart from that, the R² value obtained from the model is 0.75. This means that the economic welfare variable can be explained by 75% using participation variables in planning, implementation, and utilization of results. The conclusion above means that the greater the participation of farmers in the planning, implementation, and utilization stages, the greater the possibility that their economic welfare will also increase.